(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Latest technological developments have created the water conservation more efficient and use of chemicals a lot of restricted by introducing “Recycling reusing water practices” and “Chemical free platforms”. With limited options available to the designed and operating cooling tower, these areas could be explored for better and cost effective performance and environment friendly impact.